2019
DOI: 10.3345/kjp.2019.00150
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and management of intravenous immunoglobulin-resistant Kawasaki disease

Abstract: Kawasaki disease (KD) is a systemic vasculitis that mainly affects younger children. Intravenous immunoglobulin (IVIG) resistant cases are at increasing risk for coronary artery complications. The strategy on prediction of potential nonresponders and treatment of IVIG-resistant patients is now controversial. In this review the definition and predictors of IVIG-resistant KD and current evidence to guide management are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
(47 reference statements)
0
10
0
3
Order By: Relevance
“…Current follow up drug therapy for KD children with IVIG resistance mainly includes the second dose of IVIG, methylprednisolone (MP), infliximab, interleukin 1 receptor antagonist or cyclosporin [ 3 ]. However, KD patients who fail to respond to 2 doses of IVIG present a unique challenge [ 80 ]. A meta-analysis comprising 372 refractory KD patients conducted in 2019 by Chan et al [ 81 ] revealed that infliximab, MP, and second IVIG infusion showed no significant differences in the cardioprotective effect or the rate of treatment resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Current follow up drug therapy for KD children with IVIG resistance mainly includes the second dose of IVIG, methylprednisolone (MP), infliximab, interleukin 1 receptor antagonist or cyclosporin [ 3 ]. However, KD patients who fail to respond to 2 doses of IVIG present a unique challenge [ 80 ]. A meta-analysis comprising 372 refractory KD patients conducted in 2019 by Chan et al [ 81 ] revealed that infliximab, MP, and second IVIG infusion showed no significant differences in the cardioprotective effect or the rate of treatment resistance.…”
Section: Discussionmentioning
confidence: 99%
“…While steroids are the first line of management in most of the immune vasculitis; its use is controversial in Kawasaki disease (11,12). Intravenous immunoglobulins is the first line of management to prevent the coronary artery disease in Kawasaki disease (13). Incomplete or atypical Kawasaki disease should be taken into consideration in case of all children with unexplained fever for more than 5 days, associated with 2 or 3 of the main clinical findings of Kawasaki disease (4).…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of incomplete Kawasaki disease is based on presence of any three of the supplemental laboratory criteria: anaemia, leucocytosis, thrombocytosis, elevated alanine aminotransferase, hypoalbuminemia and sterile pyuria. Cardiac complications, mostly coronary artery aneurysm, can occur in 20% to 25% of untreated patients and in 4% of treated patients (13). Other aneurysms in different medium sized arteries are documented ( e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, some severely affected patients show a persistent fever, sustained or elevated CRP and WBC, and a higher risk of CALs. For these patients, pediatricians have used various regimens including IVIG reinfusion, methylprednisolone pulse therapy (10–30 mg/kg), anti-cytokine biologics (IL-1, IL-6, and TNF-α), potent immune-suppressor such as cyclophosphamide and plasmapheresis [ 122 ]. These treatments can induce eventual defervescence but have a limited effect on preformed aneurysms and progression of CALs since the drugs cannot control the etiological substances, and ongoing inflammation of arteritis is dependent on the immune system of the patients [ 56 ].…”
Section: Treatmentmentioning
confidence: 99%